Valencian agrarian contracts, food sovereignty and the pandemic - Ramón Fernández, Francisca (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Agricultural contracting in the Valencian Community (Spain) is related to the Huerta area and the proximity trade of agricultural products. The influence of the Valencian custom is shown in the agricultural field and has been included in the legislation analyzed. The objective of this study is to publicize the form of sale through La Tira de Contar through which the farmer promotes a local culture and food sovereignty through this unique form of transaction, and the consequences that the pandemic has had on the Valencian agricultural area. The methodology used has been the analysis of the legislation and the contribution of the doctrine on this matter. As main results we can indicate that the protection of the legislation of the agrarian contracts and of the Huerta allow the survival of a sector that has been affected by economic factors. The analyzed form of sale and the custom are maintained over time and show an example of adaptation of agriculture. The health crisis caused by the pandemic has produced negative effects, and denotes that agriculture must be subject to future modernization through new technologies.